2013
DOI: 10.1111/jonm.12084
|View full text |Cite
|
Sign up to set email alerts
|

Quality, efficiency and integrity: value squeezes in management of hospital wards

Abstract: Hybrid management may be beneficial for coping with pressure on integrity, although more empirical research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 31 publications
2
28
1
Order By: Relevance
“…While prior studies have identified a tension between system efficiency and the overall quality of care, they have only done so from the perspectives of leaders (Udod & Care , Orvik et al . ). In contrast, our study illuminates nurses’ perspectives on how leaders and nurses are challenged in reconciling these competing priorities in a specific type of care that is especially relevant to older people.…”
Section: Discussionmentioning
confidence: 97%
“…While prior studies have identified a tension between system efficiency and the overall quality of care, they have only done so from the perspectives of leaders (Udod & Care , Orvik et al . ). In contrast, our study illuminates nurses’ perspectives on how leaders and nurses are challenged in reconciling these competing priorities in a specific type of care that is especially relevant to older people.…”
Section: Discussionmentioning
confidence: 97%
“…Some authors have signaled concern for the future of nursing when organizational cultures promote too much focus on efficiencies without a better balance between economics and quality care values and professionals standards (Duncan et al 2014, Orvik et al 2015. In practice, we know that effective frontline nurse leaders strive to create this balance while also ensuring adequate resources to realize high quality care.…”
mentioning
confidence: 99%
“…Over time, feelings of being alienated to interorganizational processes and forced to do what you do not want to do may induce integrity pressure with potentially negative effects on work health and wellbeing [48]. Integrity pressure may, however, also have implications beyond individual health.…”
Section: Discussionmentioning
confidence: 99%